Deskripsi Perkembangan Keterampilan Dasar Kerja Laboratorium Kimia Siswa SMA Negeri 1 Singaraja - Kartini, Ketut Sepdyana (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aims of this study was to describe the development of basic skills students in a chemistry laboratory carrying out the work. This study was conducted using a qualitative approach with the subject of the research is 603 students consisting of 8 classes of X grade, 7 classes of XI grade and 7 classes of XII grade. Data were collected with observation papers. The results showed only 8 out of 10 aspects of the basic skills of laboratory work were observed. Five aspects of skills classified into very well categories and three categories of skills aspect quite well.